From research to real-life implementation: an evaluation of the scale up of a guided digital mental health intervention in Lebanon: Step-by-Step - Abi Ramia, Jinane; Khoury, Sally; Armani, Narsis; Cuijpers, Pim; Carswell, Kenneth; van ‘t Hof, Edith; Zoghbi, Edwina; Sijbrandij, Marit; El Chammay, Rabih (Frontiers in Public Health, 2025)
IntroductionDigital mental health interventions offer a promising approach for addressing the global mental health treatment gap. However, concerns remain regarding their effectiveness and scalability in real-world settings, particularly in crisis-affected low-and middle-income countries (LMICs). Following randomized clinical trial research, the World Health Organization’s Step-by-Step (SbS) guided digital self-help intervention for depression and anxiety was scaled up in a pilot implementation by the National Mental Health Programme (NMHP) in Lebanon. This paper outlines results from this pilot and its integration into healthcare in a setting facing political, financial, and humanitarian crises.MethodsA mixed-methods implementation study using the RE-AIM framework assessed the reach, effectiveness, adoption, implementation, and maintenance of SbS in Lebanon. Quantitative analyses evaluated clinical, satisfaction, and uptake outcomes. Forty two key informant interviews with SbS users, staff, and key stakeholders assessed the public health impact and implementation success in Lebanon.ResultsDespite contextual challenges affecting SbS’s reach and adoption, findings indicate that SbS had high uptake with 1,942 users completing the baseline assessment. Significant reduction in symptoms of depression was observed with an effect size of r = 0.69 (pre and post-tests). With a high dropout rate (62% of the starters), qualitative findings explored strategies to optimize user adherence, such as improving in-app engagement and early rapport-building. Acceptability and adoption among disseminating partners were evident yet concerns prevailed around the team’s capacity and the ability to manage risk remotely. By the end of the pilot, SbS had not yet been formally integrated into the mental health referral model but was instead provided as a national service signposted by several facilities. While global interest and funding for digital interventions present an opportunity for sustaining SbS, barriers include poor internet access, lack of sustainable financing, and the absence of a comprehensive referral model.DiscussionResults suggest that SbS has the potential to provide evidence-based treatment for depression across the whole of Lebanon, potentially as a first-step treatment within the model in primary care. Reach can be expanded through social media, mass media, and outreach. Long-term sustainability will depend on securing stable funding, robust and formal integration models, and enhancing user adherence.Clinical trial registrationThe initial clinical trial registration of the RCT phase was ClinicalTrials.gov, identifier NCT03720769.